Mind the buffering capacity of citric acid - S. R. Nozawa; I. C. Rigoli; G. Thedei Jr.; A. Rossi (Fungal Genetics Reports, 1995)
Many microbial cultures are buffered with citric acid over a pH range of 2.5 to 7.0 since the pKa values for this triprotic acid are 3.13, 4.76 and 6.40, as shown in The Merck Index (pp 330-331, 10th Edition, Martha Windholz, ed.). However, the information about the buffering range of this weak acid is controvertial since the pKa3 value may be 5.40, as specified in Day and Underwood (Quantitative Analysis, 6th Edition, 1991, p. 662. New Jersey: Prentice Hall). With this in mind, we determined the pKa values of citric acid at concentrations ranging from 5 mM to 50 mM, concentrations which are the most employed in buffers for the culture of many microorganisms.